Engaging teenagers in the english learning process - López Cárdenas, Nancy Viviana; Ordoñez Segovia, Aracely de Jesús
This monograph aims to determine the causes why ninth-grade students (12 to 13 years old) at Mensajeros de la Paz high school are not motivated during the learning process of English as a foreign language. The results found have led the authors of this project to design a booklet with a series of activities based on learning strategies which are beneficial to engage teenagers in the English learning process. This project is based on the application of a poll applied to ninth-grade students in order to know how their English class is carried on. The analysis of the data was organized in percentages, allowing the authors to find the problem. This project suggests English teachers the incorporation of cognitive and social and affective strategies to the EFL class in order to make students active participants in the learning process.